Pengaruh Program Kabar Pemilu di tvOne Terhadap Pilihan Politik Pemilih Pemula di Indonesia dalam Konteks Pemilihan Umum 2024 : Penelitian - Panggabean, Ronald H.; Mihardja, Eli Jamilah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines the influence of tvOne's Election News program on the political choices of first-time voters in the 2024 General Election. Using a qualitative approach and case study, data were obtained through interviews with four informants and an analysis of a January 10, 2024, broadcast featuring President Soeharto's use of AI. This study assesses the role of television as a traditional mass media in shaping first-time voters' political knowledge, attitudes, and preferences using the Framing Theory and Elaboration Likelihood Model (ELM) framework. The results show that first-time voters consume more political information from social media, but Election News remains influential through peripheral ELM routes such as visual packaging and formal presentation style. Informants considered the program neutral, even though its delivery style was considered vocal or serious, and they trusted social media and their social environment more. Media literacy and social interaction also moderated this influence. This research enriches the understanding of political communication in the era of media convergence and provides practical implications for media and election organizers.